Social capital dimensions for tacit knowledge sharing: exploring the indicators - Rosmah Mat Isa,; Nor Liza Abdullah,; Zizah Che Senik, (Penerbit Universiti Kebangsaan Malaysia, 2010)
The importance of social aspects of knowledge sharing has been emphasized in the literature on managing knowledge, with the recognition that knowledge is often tacit and embedded within particular social groups and situations. It is argued that the main dimensions of social capital relevant to knowledge sharing are structural, cognitive, and relational capitals. These dimensions, among other things, foster the exchange of knowledge and resources especially in settings where activity and learning are project-based. Since a project team is essentially tasked with integrating distributed knowledge, social capital of the team members is pertinent. However, understanding the relationship between social capital and knowledge integration within a project team requires that the dimensions of social capital be explicitly distinguished. Thus, the objective of this paper is to identify the dimensions and items of social capital in fostering tacit knowledge sharing among team members of projects. This study used grounded theory method and data were collected through in-depth interviews. Data were analysed using open, axial, and selective coding. This study proposes a list of social capital indicators for tacit knowledge sharing highlighting the categories and items of social capital dimensions